Functional outcome of retrograde nailing versus locked plating of extra-articular distal femoral fractures in adults: A randomized controlled trial - Yadav, Chandra Bhusan; Rajak, Asish; Shrestha, Bikram Prasad; Rijal, Raju; Maharjan, Rajiv; Kalawar, Rosan PS; Limbu, Amit (Journal of Kathmandu Medical College, 2020)
Background: Distal femoral fracture constitutes the supracondylar and intercondylar fractures of femur. These are treated by locking plates as well as with nails. Despite the widespread use of both techniques, there are only few comparative studies. The two clinical techniques used to stabilize distal femur fractures are compared in this study. Objectives: The aim of this study was to compare plating and nailing in terms of functional outcome using the Hospital for Special Surgery (HSS) Knee Score of operative fixation of extra-articular femur fracture. Methodology: A randomized controlled trial was conducted with a total of 30 patients presenting to BP Koirala Institute of Health Sciences in a period of twelve months. All skeletally mature (>16 years) adult patients with isolated traumatic closed extra-articular fracture of distal femur without distal neurovascular deficit and giving written and informed consent were included. Patients with re-fractures, poly-trauma, fracture dislocations, pathological fracture and compartment syndrome were excluded. They were operated and followed up at 2, 6, 12 and 24 weeks. Results: The demographic profiles of the two groups were comparable. There was no significant difference in functional outcome (Hospital for Special Surgery score), union or complications between them. Conclusion: This study showed that there was no significant difference in terms of functional outcome (Hospital for Special Surgery score), union, fracture alignment, range of motion (knee, hip joint), infection, other outcome measures between plating and nailing in the treatment of distal femoral fracture in adults. Hence, further study is required to come to firm conclusions.